Trade Unions in Germany: Challenges and Solutions - Alexander A. Rozhin (Современная Европа)
German trade unions traditionally play critical role in securing fair work conditions and wages. However, in the XXI century they are facing significant challenges, caused by effects of globalization, structural changes in the labor market and others. The most prominent problem is gradually declining membership and therefore shrinking resource capacity. Necessity to attract new members encourages them to undertake many different actions: from increasing protest activity to altering their work models. Author considers the cases of German trade unions and how they react to the acute issues and their connection to the protests. Author draws a conclusion that structural transformations of the labor market have been more impactful than changes in their public perception. Worker unions have remained a significant and influential force in political and social fields. Nevertheless, format of their work requires significant modifications to strengthen them as organizations that truly represent workers interests.